Expansion of Intestinal Secretory Cell Population Induced by Listeria monocytogenes Infection: Accompanied With the Inhibition of NOTCH Pathway - Zhou, Cong; Zhang, Yuanyuan; Bassey, Anthony; Huang, Jie; Zou, Yafang; Ye, Keping (Frontiers in Cellular and Infection Microbiology, 2022)
Listeria monocytogenes, as a model organism, is a causative agent of enteric pathogen that causes systemic infection. However, the interaction of L. monocytogenes and small intestinal epithelium has not been fully elucidated yet. In this study, mice and intestinal organoids were chosen as the models to investigate the influence of L. monocytogenes infection on the intestinal secretory cells and its differentiation-related pathways. Results confirmed the phenomenon of intestinal damage that L. monocytogenes infection could lead to villi damage in mice, which was accompanied by the increase of TNF-α production in jejunum as well as lipopolysaccharide (LPS) secretion in serum. Moreover, it was demonstrated that L. monocytogenes infection increased the number of goblet and Paneth cells in mice and intestinal organoids and upregulated the expression of Muc2 and Lyz. Furthermore, L. monocytogenes decreased the relative expression of Notch pathway-related genes (Jag1, Dll4, Notch1, and Hes1) while upregulating the relative expression of Math1 gene in mice and intestinal organoids. This indicated that L. monocytogenes infection caused the inhibition of Notch pathway, which may be the reason for the increased number of goblet and Paneth cells in the intestine. Collectively, these results are expected to provide more information on the mechanism of L. monocytogenes infection in the intestine.